Direct and correlated responses to chill‐coma recovery selection in Drosophila buzzatii - Bertoli, Carlos Ignacio (2010)
Chill-coma recovery (CCR) is an important trait for thermal adaptation in insects. Multiple phenotypes could be affected by selection on CCR if the trait is genetically correlated with other adaptive traits. To test for heritable (co-)variation in CCR, we examined direct and correlated responses to bi-directional selection on CCR. Drosophila buzzatii Patterson & Wheeler (Diptera: Drosophilidae) was artificially selected for decreased and increased recovery time following exposure to 0 °C. After 18 selected generations, the selection response in CCR was significant but qualitatively asymmetric, with replicated lines for slow CCR showing the highest response. Knockdown resistance to high temperature was not affected by CCR selection. Starvation resistance in the adult fly showed no clear pattern of correlated responses to CCR selection. Selection on CCR had no impact on developmental time and body size. Chill-coma recovery shows no apparent genetic trade-offs with any of the multiple traits included in this study. These results are largely consistent with recent studies on clines in D. buzzatii, which showed that CCR is not across-population correlated with other clinally varying traits of thermal adaptation. Cold adaptation may evolve toward increased cold resistance independent of upper thermal limits.